Engaging Conversationally: A Method for Engaging Students in Their Learning and Examining Instruction - Michael Kiener PhD, CRC (Park University, 2008)
Under the principles of the scholarship of teaching and learning and action research this study sought to examine how an instructor created and facilitated engagement in his students. The research was primarily undertaken to further define the middle range theory of mutual engagement. Theoretical sampling was used to analyze approximately 100 pieces of data that included instructor notes, teaching observations, feedback from conference presentations, student assessments, and end of semester student evaluations. Engaging conversationally (EC) emerged as the phenomenon that described the instructor's engagement in the learning process. EC was an ongoing cyclical pattern of inquiry that included preparing, reflecting and modeling. Interconnected in the pattern of inquiry were personality traits, counselor education, and teaching philosophy.